Centaurea cyanus extracted 13‐O‐acetylsolstitialin A decrease Bax/Bcl‐2 ratio and expression of cyclin D1/Cdk‐4 to induce apoptosis and cell cycle arrest in MCF‐7 and MDA‐MB‐231 breast cancer cell lines. Issue 10 (3rd June 2019) - Keyvanloo Shahrestanaki, Mohammad; Bagheri, Mahboobeh; Ghanadian, Mustafa; Aghaei, Mahmoud; Jafari, Seyyed Mehdi
Abstract: Natural products are considered recently as one of the source for production of efficient therapeutical agents for breast cancer treatment. In this study, a sesquiterpene lactone, 13‐O‐acetylsolstitialin A (13ASA), isolated from Centaurea cyanus, showed cytotoxic activities against MCF‐7 and MDA‐MB‐231 breast cancer cell lines using standard 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay. To find the mechanism of action of cytotoxicity, annexin V/propidium iodide (PI) staining was performed for evaluation of apoptosis. This process was further confirmed by immunoblotting of anti‐ and proapoptotic, Bcl‐2 and Bax, proteins. Cell cycle arrest was evaluated by measurement of fluorescence intensity of PI dye and further confirmed by immunoblotting of Cdk‐4 and cyclin D1. Mitochondrial transmembrane potential (ΔΨm) and generation of reactive oxygen species (ROS) were measured using the JC‐1 and DCFDA fluorescence probes, respectively. These experiments showed that 13ASA is a potent cytotoxic agent, which activates apoptosis‐mediated cell death. In response to this compound, Bax/Bcl‐2 ratio was noticeably increased in MCF‐7 and MDA‐MB‐231 cells. Moreover, 13ASA induced cell cycle arrest at subG1 and G1 phases by decreasing protein levels of cyclin D1 and Cdk‐4. It was done possibly through the decrease of ΔΨm and increase of ROS levels which induce apoptosis. In conclusion, this study mentioned that 13ASA inhibit the growth of MCF‐7 and MDA‐MB‐231 breast cancer cell lines through the induction of cell cycle arrest, which triggers apoptotic pathways. 13ASA can be considered as a susceptible compound for further investigation in breast cancer study. Abstract : 13‐O‐acetylsolstitialin A is a natural product, which was extracted from Centaurea cyanus . Herein we indicated that this compound can be considered as a susceptible cytotoxic agent against breast cancer.